PERAN MEDIASI BRAND TRUST DALAM PENGARUH CELEBRITY ENDORSER DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN SEPATU NEW BALANCE MELALUI SHOPEE DI PURWOKERTO - Imam Muzaki; Totok Haryanto; Erny Rachmawati; Meydy Fauzi Ridwan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The rapid growth of e-commerce in Indonesia has intensified competition among fashion brands on platforms like Shopee, making digital marketing strategies increasingly critical for influencing consumer purchasing decisions. This study aims to analyze the influence of celebrity endorser and online customer review on purchasing decisions for New Balance shoes on Shopee, with brand trust as a mediating variable. A quantitative explanatory survey with a cross-sectional design was employed with 204 respondents selected through purposive sampling from active Shopee users in Purwokerto. Data were collected via online questionnaires using a 5-point Likert scale and analyzed using PROCESS Macro Hayes Model 4 with 5,000 bootstrap resamples at a 95% confidence level. The results indicate that celebrity endorser has a positive and significant effect on brand trust, with a coefficient of 1.0351. Brand trust has a positive and significantly influences purchasing decisions and mediates the relationship between celebrity endorser and purchasing decisions, with an indirect effect of 0.6449. Online customer review has a positive and significant direct effect on purchasing decisions, with a coefficient of 0.9487, without being mediated by brand trust. The model explains 87.75% of the variance in purchasing decisions, indicating that brand trust serves as a significant mediator between celebrity endorser and purchasing decisions.